Athletic Performance and Psychological Resilience - Akram, Muhammad; Maqbool, Tahmina; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
This study investigates how higher psychological resilience and physical performance are enabled by mental development, mental hardness, lexical memory, and conditional motivation. It investigates how the psychological factors enable long-term motivation, disease avoidance, and mental improvement—factors that all come together to make the athlete more resilient both psychologically and physically.